Efektifitas Penggunaan Pendekatan Pembelajaran Berbasis Masalah (Problem Based Learning) dalam Pembelajaran Matakuliah Metodologi Penelitian Bahasa Arab - Ainin, Moh. (citeus, 2017)
The aim of this research is to describe the effectiveness of using Problem Based Learning (PBL) approach in Arabic Language Research Method Class. It uses a quasi-experimental (pre- experimental design). The result shows that generally using PBL is effective in both aspects of the learning process and the learning outcomes. The specific findings in this research is that the using PBL is not effective for students in the lower class category both from the aspect of competence, learning attitude, willingness to learn, learn discipline, and activeness in class.